Nuevo registro de la rana en peligro de extinción lithobates johni en la huasteca y consideraciones sobre su distribución actual - Campos-Rodríguez, José Ismael; López-Galicia, Florence Lizeth; Flores-Leyva, Xhail (Instituto de Ecología, A.C., 2012)
We provide an additional locality for L. johni from the Huasteca region and an overview of the current range of this species.